Taxonomic identity of the patagonian frog Atelognathus jeinimenensis (Anura: Neobatrachia) as revealed by molecular and morphometric evidence - Díaz-Páez, Helen; Vidal, Marcela A.; Ortiz, Juan C.; Úbeda, Carmen A.; Basso, Néstor G. (Zootaxa, 2011)
The frog genus Atelognathus is currently represented by nine species distributed in Argentinean and Chilean Patagonia. It is mainly distributed in Argentina, and there are only three species in Chile (A. ceii, A. grandisonae and A. jeinimenensis). Regarding the morphological relationships among Atelognathus species, Meriggio et al. (2004) suggest that A. jeinimenensis is more related to A. salai than other species. A. salai was described from Laguna Los Gendarmes (Argentina), 90 km air line from the type locality of A. jeinimenensis. This paper presents a morphological analysis and a study of population genetics using mtDNA nucleotide data from Argentinean and Chilean localities to assess the genetic distance between A. salai and A. jenimenensis. We obtained 477 bp-long d-loop sequences from 51 Atelognathus specimens collected in four localities. According to our results, the morphological differences between A. salai and A. jeinimenensis populations are limited to size, and there are no distinctive characteristics that would separate two species, in addition to which a simple geographic pattern of genetic diversity suggests a single species of Atelognathus. Also, the populations from Chile (Cerro Castillo, RN Lago Jeinimeni and Chile Chico) and Argentina (Laguna de Los Gendarmes) have low levels of genetic divergence that may be consistent with glaciations during the Late Pleistocene. We propose Atelognathus jeinimenensis as a junior synonym of A. salai and that the Chilean populations should be assigned to A. salai.